The cardiazol shock and its relation to experimental catatonia - Gutiérrez Noriega, Carlos (1938)
1. cardiazol offers shock in dogs and roosters in the following periods: psychomotor excitement, seizures, balance disorders and catatonia. The first period in turn comprises the tonic, clonic phase, inertia interval and swimming motions. The latter are subject to special considerations. Process differences are apparent in the two species studied. 2. tonic and clonic movements and swimming would be different processes from each other in origin and mechanism of action. 3 Periods of motor inhibition and catatonia comprise a series of functional disturbances ranging from coma to catalepsy, and are regarded as manifestations of a process of functional ecovering or disinhibition that radiates from the caudal to the cephalic extremity. 4. Cardiazol acts as psychokinetic moderate doses and at higher doses as convulsant and psicopléjico. 5. found relationships between individual constitution and the type of shock. Each animal plays a form of shock invariably finding the characteristic especially in the third and fourth periods. In response to this observation, we divided the catatonic-labile and catatonic-resistant, classification is also based on the susceptibility of the nervous system of each agency to the functional state of disintegration and catatonía.6. Status epilepticus produced by Cardiazol in dogs was studied. One of the most dangerous manifestations in the course of it is the significant hypotension.